2013
DOI: 10.1039/c3an01379k
|View full text |Cite
|
Sign up to set email alerts
|

Revisit of a dipropargyl rhodamine probe reveals its alternative ion sensitivity in both a solution and live cells

Abstract: This study reveals that a dipropargyl rhodamine B derivative previously described as a reaction-based irreversible palladium probe responds, however, more sensitively to mercury with a reversible "turn-on" fluorescence. The probe also shows a much better imaging ability for mercury than for palladium in live cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…30 Here, we use the CuAAC click reaction to simply couple 1 with a water-soluble PEG tail to enhance the water solubility. In addition, since the as-formed bis-triazolyl motif is envisioned to chelate more strongly and selectively a metal ion, 34−41 a monotriazolyl PEG rhodamine derivative was synthesized for analyzing the structure activity relationship.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Here, we use the CuAAC click reaction to simply couple 1 with a water-soluble PEG tail to enhance the water solubility. In addition, since the as-formed bis-triazolyl motif is envisioned to chelate more strongly and selectively a metal ion, 34−41 a monotriazolyl PEG rhodamine derivative was synthesized for analyzing the structure activity relationship.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Compounds 1, 30 13 4 , and Cu(ClO 4 ) 2 were prepared in deionized water. The fluorescence measurements were carried out with a path length of 10 mm and an excitation wavelength at 530 nm by scanning the spectra between 540 and 750 nm.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…38 This is mainly due to the difficulty in glycosylation of phenolic alcohols with other hexoses. [39][40][41][42][43] In particular, L-fucose as a 6-deoxy sugar is more electron rich than its parent hexose hence more prone to hydrolysis of its glycosidic bond. [44][45] As a consequence, a new platform strategy for visualizing a more diverse range of glycosidases implicated in the myriad of biologically and pathologically important cellular events is highly needed.…”
Section: Introductionmentioning
confidence: 99%
“…Some interesting studies on this "OFF-ON" type of uorescent sensors have been reported since Czarnik's pioneering work on the breaking of the spirolactum ring of rhodamine B derivative in the presence of Cu 2+ afforded strong uorescence. [42][43][44][45][46][47][48][49][50][51] Particularly, only few reports were available on detection of aluminium or uoride. [52][53][54][55] Besides, 8hydroxyquinoline is a kind of important chelators for metal ions and has been widely used to construct functional ionophores for recognizing metal ions.…”
Section: Introductionmentioning
confidence: 99%